Penentuan Suhu Dan Waktu Optimum Pada Tahap D0 (Delignifikasi Pertama) Proses Bleaching Pembuatan Pulp - Sembiring, Maria Peratenta; Silaban, Kardiman; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
PT. Riau Andalan Pulp and Paper (RAPP) is a company has produced pulp and paper with Elemental Clorine Free (ECF) system in bleaching pulp stage. PT. RAPP used four process bleaching stage of pulp that’s D0 – EP - D1 – D2. Using clorine dioxide (ClO2) as bleaching pruff but EP stage were lignin extract process using oxygen and sodium dioxide (NaOH). One of the important thing in bleaching pulp is D0 stage process. For producing high quality pulp, one of important pruff must be recheck is temperature and time of bleaching pulp. The purpose of research was knowing effect of temperature in cooking timeof the first bleaching pulp stage process with accasia to quality pulp and economic value. Result of research to be used with get variation bleaching time 60, 70, 80, 90, 100 and 120 minutes and get variation bleaching temperature 65, 75, 80, and 90 (0C). in 650C and 60 minutes brightness was produced higher than else that is 66.42% ISO.